The Design of Mathematics Learning with A Problem Based Learning Scheme to Stimulate Students' HOTS - Riawan Yudi Purwoko; Jayanti Putri Purwaningrum; Syaza Hazwani binti Zaini; Agung Slamet Kusmanto (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
The need for effective mathematics learning is closely tied to the availability of instructional tools that can foster students' higher-order thinking skills (HOTS). However, such tools remain limited, particularly within vocational education settings. This study aims to develop mathematics learning instruments based on a problem-based learning (PBL) approach that are valid, practical, and effective in enhancing HOTS among vocational high school students. The developed products intended for Grade XI students in the second semester consist of lesson plans, student activity sheets, and learning outcome test instruments. The research employed a 4-D development model, consisting of the stages of define, design, develop, and disseminate. The instruments were tested through three phases: expert review, limited trial, and field trial. Participants included mathematics teachers and students from two different vocational schools. Data were collected using validation sheets, teacher and student assessment instruments, and learning outcome tests. The findings indicate that the developed instruments meet all three criteria: validity, practicality, and effectiveness. Expert validation confirmed that the lesson plans and student activity sheets are valid, the limited trial showed that the tools are practical for classroom use, and the field trial demonstrated that the instruments effectively improved students’ HOTS. In conclusion, the developed mathematics learning instruments not only provide an empirically tested and innovative alternative to conventional teaching methods but also contribute significantly to strengthening vocational mathematics education. By promoting students’ HOTS, these tools help prepare learners with essential 21st-century competencies.